Specific Targeted Integration of Kanamycin Resistance-Associated Nonselectable DNA in the Genome of the Yeast Saccharomyces cerevisiae. (May 2003) - Waghmare, Sanjeev K.; Caputo, Valentina; Radovic, Slobodanka; Bruschi, Carlo V.
Sophisticated genome manipulation requires the possibility to modify any intergenic or intragenic DNA sequence at will, without leaving large amounts of undesired vector DNA at the site of alteration. To this end, a series of vectors was developed from a previous gene knockout plasmid system to integrate nonselectable foreign DNA at any desired genomic location in yeast, with a minimum amount of residual plasmid DNA. These vectors have two mutated Flp recognition targets ( FRT ) sequences flanking the KanMX4 gene and multiple sites for subcloning the DNA fragment to be integrated. The selectable marker can be recycled by Flp site-specific excision between the identical FRT s, thereby allowing the integration of further DNA fragments. With this system, the NLS-tetR-GFP and DsRed genes were successfully integrated at the thr1 locus, and the RVB1 gene was tagged at the C-terminus with the V5-epitope-6-histidine tag. This plasmid system provides for a new molecular tool to integrate any DNA fragment at any genome location in [ cir + ] yeast strains. Moreover, the system can be extrapolated to other eukaryotic cells in which the FLP/FRT system functions efficiently.